Shush! : growing up Jewish under Stalin : a memoir - Draitser, Emil, 1937- (S. Mark Taper Foundation imprint in Jewish studies., 2008)
"The old man wears a skullcap, and I m puzzled and secretly irritated: why declare to everybody that you re a Jew?" Growing up in Odessa in Soviet Ukraine in the post-Holocaust years, under Stalin, Draitser despises his Jewish identity. Mocked at school, he absorbs the virulent anti-Semitism. He hates Yiddish. Now a professor of Russian at Hunter College in New York, he looks back, blending historical overview with a present-tense narrative of how it feels to be a child taught to despise his culture. More than the commentary, the unforgettable drama--and the answer to the racism--is the celebration of Jewish family life and the richness of Yiddish, from the curse words to the endearments. Papa, a house-painter, is always looking for a famous Jew to celebrate. But the hero is Mama, labeled "dependent" on the official papers, but the true head of the family in their crammed one-roomed apartment, her cooking an expression of love, even when it seems excessive: "Take some more. It's good for you." Copyright 2008 Booklist Reviews